Role of microbes in plant protection using intersection of nanotechnology and biology - Kaushal, M. (Springer, 2018)
Plant pathogens are one of the dominating components which restrain crop productivity. Preliminary step headed for managing plant disease is to accurately recognize the pathogen under lab, glasshouse, and field conditions. Modern approach, such as culture-based, antibody-based rapid methods and quantitative polymerase chain reaction (Q-PCR), entrusts on multiple assays to precisely identify the specific plant pathogens which are further time-consuming and lack high sensitivity. Nanobiotechnology ameliorates crop productivity through transmission of genes to target sites for breeding of varieties resistant to different plant pathogens with focus on improving sensitivity. Intersection of nanotechnology and biology also improves specificity and agility of pathogen detection which further facilitates crop disease management. Bio-fabrication of nanoparticles like silver (Ag) and copper (Cu) is used as novel antimicrobials for the management of pathogenic microorganisms that inhibits fungal hyphae and conidial germination in agricultural crops. Biological agents reduce metal which leads to capping of nanoparticles through the secretion of various enzymes. A modern class of protein nanocompartments called as encapsulins that encapsulate cargo proteins are found in bacteria and archaea. Nanobiotechnology also reduces detection times of crop pathogens and cost by the development of biosensors and phage proteins. In this chapter we emphasize on microbial semblance in nanobiotechnology applications that precede to integrated disease management of agricultural crops including precise diagnostic layout of plant diseases and modification of crop environments to adversely affect crop pathogens.